TINGKAT LITERASI SUKUK MAHASISWA EKONOMI ISLAM (STUDI DI UNIVERSITAS ISLAM INDONESIA DAN UNIVERSITAS DARUSSALAM GONTOR) - Miftahul Huda; Achmad Fajaruddin; Nafisatu Roudlotin Ni’mah (Journal of Islamic Economics and Philanthropy, 2021)
The majority of Indonesia’s Muslim population cannot increase capitalization in the sharia capital market. Compared to other Asian countries, Indonesia should have more potential to increase the number of investor Sukuk in the sharia capital market given the large population of Muslims in Indonesia. The problem that arises a lot among students is the lack of a fixed income and still very dependent on parents and wasteful attitudes on spending money that is less important. Sukuk can be one of the paths to develop the sharia economy. Investment based on sharia principles provides a great opportunities and ease in their implementation, it make Sukuk an excellent opportunity to be amendable. This study aims to measure the Sukuk literacy rate of Islamic economic college students for private Islamic universities. This study distributed 169 questionnaires and was shared in Islamic University of Indonesia and University of Darussalam Gontor to compare the Sukuk literacy rate between two universities. The data analysis method used by this research is descriptive analysis percentage. The result showed in this study is that the Sukuk literacy rate in both universities is in the medium category looked to the score of Islamic University of Indonesia 66,62 and to the University of Darussalam Gontor that is 60,58. However even though they belong in the same category, the percentage rate in the Islamic University of Indonesia is higher than the University of Darussalam Gontor.